The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2004
DOI: 10.1038/sj.onc.1208039
|View full text |Cite
|
Sign up to set email alerts
|

Demonstration of tumor suppression by mannose 6-phosphate/insulin-like growth factor 2 receptor

Abstract: The mannose 6-phosphate/IGF-2 receptor has been proposed to be a tumor suppressor gene on the basis of loss of heterozygosity and mutations in tumors from cancer patients. To test this hypothesis, the receptor was expressed in 66cl4, a mouse mammary tumor cell line deficient in the receptor. Expression of the receptor corrected the abnormal lysosomal trafficking phenotype displayed by these cells. Receptor expression had no apparent effect on growth or invasiveness of the cells in vitro but effectively inhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0
5

Year Published

2006
2006
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 44 publications
1
22
0
5
Order By: Relevance
“…24 In contrast, subnormal levels of ectopically expressed M6P/IGF2R did not affect the motility of receptor-deficient murine mammary tumour cells. 25 In the case of SCC-VII cells, the migratory response of M6P/IGF2R-positive cells was consistently lower than that of their parental counterparts, even though the former displayed near physiological M6P/IGF2R levels. These results indicate that the M6P/IGF2R status affects the ability of squamous cell carcinoma cells to penetrate ECM barriers.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…24 In contrast, subnormal levels of ectopically expressed M6P/IGF2R did not affect the motility of receptor-deficient murine mammary tumour cells. 25 In the case of SCC-VII cells, the migratory response of M6P/IGF2R-positive cells was consistently lower than that of their parental counterparts, even though the former displayed near physiological M6P/IGF2R levels. These results indicate that the M6P/IGF2R status affects the ability of squamous cell carcinoma cells to penetrate ECM barriers.…”
Section: Discussionmentioning
confidence: 89%
“…26 For choriocarcinoma and breast tumour cells, the growth-suppressive capacity of M6P/ IGF2R has been also verified in vivo. [23][24][25] It is thought that the anti-proliferative activity of M6P/IGF2R in tumour cells is mainly due to its impact on IGF-II signalling. 24,44 Wise and Pravtcheva have demonstrated that the presence of an Igf2r transgene delays Igf2-induced mammary tumour formation in mice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To this end, we used the 4T1-Luc syngeneic metastatic mouse breast cancer model (24)(25)(26)(27). This model is based on the 4T1-Luc mouse mammary tumor cell line, which when injected intravenously disseminates to distant organs, homing to lungs, liver, bone, and brain over a short period of time.…”
Section: Archazolid Inhibits Metastasis In Vivomentioning
confidence: 99%
“…We then tested whether the phenotypes observed are due to increased ligand supply by the introduction of a bovine keratin 10-driven transgene expressing a soluble full-length mouse Igf2r (K10DIgf2r), previously shown to act as a ligand trap and to limit IGF-II bioavailability (23,(34)(35)(36)(37).…”
Section: Introductionmentioning
confidence: 99%